Buda Tārā: surgimento, transformação e permanência da centralidade de um ícone feminino no budismo tibetano Geluk - Marques, Tattiane Yu Borges (2022)
This work aims to understand how the narratives of the emergence and transformations of Buddha Tārā are consolidated in the Geluk of Tibetan Buddhism, to investigate which impacts are caused by this female icon so important in the Tibetan Buddhism. Her emergence is consolidated in the movements of the tantric system, in India, from the VI century, where the contextualization becomes quite complex, considering the rich cultural interweaving of beliefs of the tantra system in ancient Indian society. To analyze her emergence, the diachronic methodology that turns to archeological and canonical texts will be used. For the concept and literary analysis, the methodology will be synchronous, privileging the literary narrative and her transformations with what we have today. For the iconographic interpretation, we will use the mapping methodology proposed by Gillian Rose, specifically the compositional and social modalities. Beyond Indian borders, when the figure of Tārā strengthened in Tibet, she is the great precursor of a popular movement in the conceptual and revolutionary spheres, which places women on an equal footing with men in terms of their achievements and conquests. A few decades later, her cult was established in the Mahāyāna Geluk tradition, reaffirming the theological vision of equanimity (upekṣā) and compassion (karuṇā), according to which it is necessary to enter the path of the Bodhisattva, whose practice is the cultivation of bodhicitta - the mind that seeks complete awakening not only for herself but for the benefit of all being. In the theology of Vajrayāṇa systems, which is an offshoot of the Mahāyāna, the Tibetan iconographies of Tārā, in her numerous representations, elevate Tārā's status as Buddha, reaffirming the hermeneutical foundations of the Mahāyāna Geluk tradition, but in practice the Geluk tradition does establish equality between men and women. We discovered, through the efforts of Buddhist researchers, that the main problem lies in the institutional educational system of Tibetan society and, mainly, in the religious educational system that deprived women for centuries of the formal study that would enable and encourage them to be minimally on their equal standing with men.(AU)